FAKTOR-FAKTOR YANG MEMPENGARUHI GANGGUAN MENTAL EMOSIONAL PADA MAHASISWA KEDOKTERAN DI FK UPN VETERAN JAKARTA TAHUN 2020 - Anisya Zakiyyahaya Arvant (2020)
Mental distress is a public health problem which refers to common mental disorders such as anxiety, depression, and somatic symptoms. It is reported that university students tend to have higher levels of mental distress compared to the general population, especially medical students because they experience high levels of stress compared to other majors. This study aimed to determine the prevalence of mental distress and its associated factors. A cross-sectional study was conducted among preclinical medical students at UPN Veteran Jakarta in June 2020. This study used proportional stratified sampling to complete questionnaires including demographic characteristics, adverse childhood experiences (ACE), family APGAR, and self-reporting questionnaire (SRQ-20). Among 138 participants, 36,2% had at least 1 or more ACEs, 55,1% of students came from a family with dysfunction, and 36,2% experienced mental distress. In multivariable regression model, factors significantly associated with mental distress are gender (OR=12,059, 95%CI), adverse childhood experiences (OR=3,080, 95%CI), family function (OR=2,733, 95%CI), and family structure (OR=0,290, 95%CI). Women, the presence of adverse childhood experiences, family with dysfunction, and non-intact family structure are more likely to have mental distress. This study recommends counselling and awareness to build a healthy family environment.